Biodistribution of mesenchymal stem cell-derived extracellular vesicles in a model of acute kidney injury monitored by optical imaging - GRANGE, CRISTINA (D.A. Spandidos, 2014)
Mesenchymal stem cells (MSCs) contribute to the recovery of tissue injury, providing a paracrine support. Cell-derived extracellular vesicles (EVs), carrying membrane and cytoplasmatic constituents of the cell of origin, have been described as a fundamental mechanism of intercellular communication. We previously demonstrated that EVs derived from human MSCs accelerated recovery following acute kidney injury (AKI) in vivo. The aim of the present study was to investigate the biodistribution and the renal localization of EVs in AKI. For this purpose, two methods for EV labeling suitable for in vivo tracking with optical imaging (OI), were employed using near infrared (NIR) dye (DiD): i) labeled EVs were generated by MSCs pre-incubated with NIR dye and collected from cell supernatants; ii) purified EVs were directly labeled with NIR dye. EVs obtained with these two procedures were injected intravenously (i.v.) into mice with glycerol-induced AKI and into healthy mice to compare the efficacy of the two labeling methods for in vivo detection of EVs at the site of damage. We found that the labeled EVs accumulated specifically in the kidneys of the mice with AKI compared with the healthy controls. After 5 h, the EVs were detectable in whole body images and in dissected kidneys by OI with both types of labeling procedures. The directly labeled EVs showed a higher and brighter fluorescence compared with the labeled EVs produced by cells. The signal generated by the directly labeled EVs was maintained in time, but provided a higher background than that of the labeled EVs produced by cells. The comparison of the two methods indicated that the latter displayed a greater specificity for the injured kidney.